The underground culinary tour : how the new metrics of today's top restaurants are transforming how America eats - Mogavero, Damian; D'Agnese, Joseph (Crown Business, 2017)
Explores how the restaurant business is transitioning away from intuitive methods toward data-driven practices, citing the examples of successful celebrity-run restaurants and culinary trendsetters to explain how modern eateries are pioneering effective new approaches.